NEED ANALYSIS ON TEACHING MARITIME ENGLISH FOR NAUTICAL STUDENTS AT POLTEKPEL SURABAYA: CURRENT PRACTICES AND FUTURE DIRECTIONS - Faradillah, Ita (CV. Lafadz Jaya, 2025)
The increasing globalized maritime industry has underscored the importance of Maritime English (ME) for nautical students, equipping them with the communication skills essential for safe and efficient operation at sea. This study aims to perform a need analysis on the teaching of Maritime English for nautical students at Poltekpel Surabaya, focusing on both the existing curriculum and the future needs of students. The research examines current instructional practices, identifies gaps between curriculum delivery and industry requirements, and proposes recommendations for enhancing Maritime English teaching. Data were collected through interviews with maritime instructors, surveys with students, and analysis of course syllabus. The findings highlight a discrepancy between the level of Maritime English proficiency required by the industry and the current state of teaching at Poltekpel Surabaya. It also discusses the relevance of existing teaching materials, the integration of modern technological tools, and the necessity for a more immersive and communicative approach to ME instruction. The study concludes with actionable suggestions for improving the quality of Maritime English education, aiming to ensure that graduates are better prepared for the demands of the international maritime industry.